(untitled) (Research, Society and Development, 2023)
Economically viable and readily accessible solutions are necessary for the sustainability of the economic endeavors of small-scale frog producers. An experiment was conducted with the objective of assessing the growth of post-metamorphosis frogs in adapted polyethylene water tanks in the period from fall to spring in the Southern Hemisphere. A total of 23 animals were employed, with a stocking density of 33 animals/m2, exhibiting an average weight of 17.39 g. The frogs were housed in a 500-L polyethylene water tank that was adapted to allow complete drainage at its outlet. The water was consistently replaced before each feeding, and the animals were provided with two daily feedings of commercial carnivorous fish food containing 400 g/kg of crude protein. Biometric measurements were conducted on 12 occasions, along with individual weighing of the frogs. The evaluated parameters included body growth (g), weight gain (g/day), feed intake (g), and feed conversion (g/g). Additionally, production costs were evaluated. Body weight (g) data were subjected to exponential regression analysis. The growth curve of the bullfrog adhered to the exponential regression model. Frog growth during the fall and winter seasons was sluggish, but, began to accelerate as spring emerged, closely associated with ambient temperature. Feed conversion rate stood at 1.89 g/g. The use of polyethylene water tanks shows promise as a viable environment for frog farming, particularly for small-scale producers.